Altering Dietary Soluble Protein Levels With Decreasing Crude Protein May Be a Potential Strategy to Improve Nitrogen Efficiency in Hu Sheep Based on Rumen Microbiome and Metabolomics - Zhang, Zhenbin; Shahzad, Khuram; Shen, Sijun; Dai, Rong; Lu, Yue; Lu, Zhiqi; Li, Chuang; Chen, Yifei; Qi, Ruxin; Gao, Pengfei; Yang, Qingyong; Wang, Mengzhi (Frontiers in Nutrition, 2022)
Ruminants account for a relatively large share of global nitrogen (N) emissions. It has been reported that nutrition control and precise feeding can improve nitrogen efficiency of ruminants. The objective of the study was to determine the effects of soluble protein (SP) levels in low-protein diets on growth performance, nutrient digestibility, rumen microbiota and metabolites, as well as their associations of N metabolism in fattening Hu sheep. Approximately six-month-old, 32 healthy fattening male Hu sheep with similar genetic merit and an initial body weight (40.37 ± 1.18 kg) were selected, and divided into four groups (n = 8) using a completely randomized design: the control diet (CON) with a 16.7% CP content was prepared to meet nutritional requirements of fattening sheep (BW 40 kg, ADG 200-250 g/d) according to the NRC recommendations, other three include low protein diets (LPA, LPB and LPC) of CP decreased by ~10%, with SP proportion (%CP) of 21.2, 25.9 and 29.4 respectively. The feeding trial lasted for 5 weeks including the first week of adaptation. The results showed no difference in growth performance (P>0.05); DM and CP digestibility were higher in LPB and LPC, with maximum organic matter digestibility in LPB (P<0.05). Low-protein diets decreased serum urea-N whereas urinary urea-N was lower in LPB and LPC (P<0.05), while N retention and biological value of N were higher in LPB and LPC (P<0.05). Ruminal NH3-N concentration decreased in LPA and LPB compared with CON, TVFA, acetate, propionate and butanoate were all lower in LPA (P<0.05). In rumen microbiome, LPB increased the community richness in Prevotellaceae and Prevotella_1 (P<0.05); Metabolomics analysis revealed low-protein diets down-regulated amino acid metabolism pathways, while biosynthesis of unsaturated fatty acids along with vitamin B6 metabolism were up-regulated with increased SP. These findings could help us to understand the role of different SP levels in the regulation of rumen microbial metabolism and N efficiency. Overall, low-protein diets (CP decreased by ~10%) can reduce serum urea-N and ruminal NH3-N without affecting the growth performance of fattening Hu sheep. Additionally higher N efficiency was obtained with SP proportion of 25~30%.